K Is for kissing a cool kangaroo - Andreae, Giles; Parker-Rees, Guy (New York : Scholastic, 2002)
Illustrations and a simple rhyme introduce all the letters of the alphabet, and the word list that follows challenges the reader to go back and find more examples of words that begin with each letter.
F
b
b
Keywords: Alphabet book -- Beginning of the year -- Animals